Changes in the Long-Term Geophysical Eruptive Precursors at Piton de la Fournaise: Implications for the Response Management - Peltier, Aline; Villeneuve, Nicolas; Ferrazzini, Valérie; Testud, Séverine; Hassen Ali, Theo; Boissier, Patrice; Catherine, Philippe (Frontiers in Earth Science, 2018)
Anticipating eruptions early enough to give warning to authorities is one of the main goals in volcanology. However, identifying and providing unequivocal identification on volcano reawakening remain challenging issues, mostly when unrests are sudden or “silent”. At the Piton de la Fournaise volcano, a clear increase in both the seismicity and the ground displacements are systematically observed a few days/weeks before eruptions, and appear as clear eruptive precursors. A systematic study of these long-term precursors demonstrates the changes in their intensity, duration and time of appearance during 1998-2017 (43 eruptions), directly linked to the influence of the pre- and post-summit caldera formation (April 2007) and to changes in the deep magma refilling process since 2016. These changes in the precursors were not without consequence on the early alert to the authorities, with some false alerts and late alerts. It is thus of prime importance for crisis management to bear in mind the possibility of these rapid changes and that of sudden volcanic unrest with little warnings, to be able to take the most appropriate decisions, in particular raising the level of alert or lifting it totally. The findings of this study have enabled the relevant authorities to improve the alert chain protocol, and scientists to communicate more efficiently with the decision-makers.